Advances in Using Hansenula polymorpha as Chassis for Recombinant Protein Production - Manfrão-Netto, João Heitor Colombelli; Gomes, Antônio Milton Vieira; Parachin, Nádia Skorupa (Frontiers in Bioengineering and Biotechnology, 2019)
The methylotrophic yeast Hansenula polymorpha, known as a non-conventional yeast, is used for the last thirty years for the production of recombinant proteins, including enzymes, vaccines, and biopharmaceuticals. Although a large number of reviews have been published elucidating the applications of this yeast as a cell factory, the latest was released about ten years ago. Therefore, this review aimed at summarizing available information on the use of H.polymorpha as a host for recombinant protein production in the last decade. Examples of chemicals and virus-like particles produced using this yeast also are discussed. Firstly, the aspects that feature this yeast as a host for recombinant protein production are highlighted including the techniques available for its genetic manipulation as well as strategies for cultivation in bioreactors. Special attention is given to the novel genomic editing tools, mainly CRISPR/Cas9 that was recently established in this yeast. Finally, recent examples of using H.polymorpha as an expression platform are presented and discussed. The production of human Parathyroid Hormone (PTH) and Staphylokinase (SAK) in H.polymorpha are described as case studies for process establishment in this yeast. Altogether, this review is a guideline for this yeast utilization as an expression platform bringing a thorough analysis of the genetic aspects and fermentation protocols used up to date, thus encouraging the production of novel biomolecules in H.polymorpha.